Occurrence and recoverability of shale oil in Paleogene formation, Subei Basin - Jin-Ning, Peng; Chongjiao, Du; Longlong, Li; Mingzhe, Deng (Frontiers in Earth Science, 2025)
In recent years, significant breakthroughs have been made in the exploration and development of lacustrine shale oil, but the stable and guaranteed production of shale oil still faces huge challenges. Quantitative characterization of the occurrence state of shale oil and accurate evaluation of the movable oil content are the key scientific issues that need to be solved for the efficient exploration and development of lacustrine shale oil. The second and fourth sections of the Funing Formation in the northern Jiangsu Basin are preferred layers for the exploration and development of continental shale oil in eastern China. However, there are few reports on the occurrence status and availability of shale oil in these areas. This study systematically investigates the oil-bearing characteristics and mobility mechanisms of shale and interlayer systems in the second and fourth membersof the Funing Formation (E1f2, E1f4), Subei Basin, through an integrated approach combining multi-temperature pyrolysis, nuclear magnetic resonance (NMR) analysis, and limited production data from 23 wells. Key findings reveal:1) Shale matrices exhibit low total retained oil content (<5.0 mg/g), dominated by adsorption-miscible oil (40%–95% of total hydrocarbons), with its proportion inversely correlated to burial depth (R2 = 0.78). Light free oil content remains exceptionally low (<0.1 mg/g), yielding a mobility ratio <3%. In contrast, interlayers and adjacent sandstones demonstrate significantly higher oil saturation (>5 mg/g), predominantly as free-phase oil (60%–82%), with light free oil exceeding 0.25 mg/g and mobility ratios of 4–7%—comparable to pre-stimulation Bakken tight sandstones (5%); 2) NMR-derived T2 cutoff values (6 m) and throat radius thresholds (>0.18 μm) indicate movable shale oil primarily resides in fracture networks (contributing 68%–85% of permeability) and secondary micropores. Phase-state analysis reveals free oil > adsorbed oil within these conductive pathways, corroborated by production data from fractured carbonate reservoirs.3) Fractured lacustrine carbonates exhibit high initial yields (e.g., Well XuX38: 15.8 t/d) but rapid decline rates (68% within 90 days). Conversely, intra-source interlayer systems demonstrate sustained production (Well TianX96: <15% decline over 18 months), attributed to stable pressure maintenance and effective matrix-fracture connectivity. Economic analysis suggests 2.1× higher EUR (Estimated Ultimate Recovery) in interlayer systems compared to fractured carbonates.